Navigating the Trauma of Change - Kent Crookston (Academic Chairpersons Conference Proceedings, 2017)
Academic leaders have identified “dealing with change” as the second of their top concerns. Dr. Crookston researched and experienced first-hand the “change characters” that emerge from within any group faced with restructuring or innovation. Participants leave this workshop better able to anticipate, understand, and work effectively with the range of personalities that react and adapt differently to change.
Keywords: dealing with change; restructuring; academic leaders